2015
DOI: 10.1007/s10620-015-3589-9
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Syndecan-1 Levels Are Elevated in Patients with Inflammatory Bowel Disease

Abstract: Our results suggest that soluble syndecan-1 is potentially a novel diagnostic marker in the management of inflammatory bowel disease patients. Its applicability as a surrogate, prognostic biomarker remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
3
20
1
Order By: Relevance
“…These above results are consistent with those found in patients with Crohn's disease (CD), which demonstrated the decreased levels of SDC1 in the intestinal mucosa and the increased levels of its ectodomain in the serum . However, our results are different from a recent study performed by Israeli researchers, which showed elevated levels of soluble SDC‐1 in CD patients, but no difference between UC patients and healthy controls . The causes of the differentiated outcomes between Israeli patients and our study were unknown yet.…”
Section: Discussioncontrasting
confidence: 99%
“…These above results are consistent with those found in patients with Crohn's disease (CD), which demonstrated the decreased levels of SDC1 in the intestinal mucosa and the increased levels of its ectodomain in the serum . However, our results are different from a recent study performed by Israeli researchers, which showed elevated levels of soluble SDC‐1 in CD patients, but no difference between UC patients and healthy controls . The causes of the differentiated outcomes between Israeli patients and our study were unknown yet.…”
Section: Discussioncontrasting
confidence: 99%
“…(13) Clinical studies in patients with inflammatory bowel disease have shown that Crohns patients had significantly reduced intestinal syndecan-1 that correlated with disease severity. (17) Yablecovitch et al demonstrated elevated levels of soluble syndecan-1 in serum of patients with both Crohn's and ulcerative colitis. (18) These studies highlight the important and newly appreciated role of syndecan-1 in intestinal pathology.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, IBD patients had higher soluble SDC-1 levels compared to healthy controls in the research by Yablecovitch et al However, in the same study, no correlation was found in SDC-1 between CRP and disease activity in contrast to our study. The reason for this difference may be attributed to the presence of large group of UC patients which has no significant difference in SDC-1 levels with the healthy controls in the subgroup analysis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%